2006
DOI: 10.1007/s10499-006-9050-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of varying dietary protein levels on growth and production of Chanos chanos (Forsskal) in inland saline groundwater: laboratory and field studies

Abstract: Two experiments were conducted to investigate the effects of varying dietary protein (35-45%) and energy levels (17.34-19.44 kJ g )1 ) on the growth performance of milkfish (Chanos chanos) maintained under laboratory (experiment 1) and field conditions (Experiment 2) in inland saline groundwater. The results of experiment 1 (initial weight of fish: 0.25 g) revealed that, irrespective of the protein source (fish meal or processed full fat soybean), fish fed a diet containing 40% protein showed significantly (p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 43 publications
(43 reference statements)
6
15
0
Order By: Relevance
“…However, increasing dietary protein level had no effect on fish body protein proportion. Similar findings were reported for various fish species, which also show no effect of dietary protein level on body protein levels (Jana et al 2006;Salhi et al 2004). Apparently, as long as the fish are getting enough energy for maintenance from nonprotein sources, and enough protein for production, their body protein content will not change.…”
Section: Discussionsupporting
confidence: 82%
“…However, increasing dietary protein level had no effect on fish body protein proportion. Similar findings were reported for various fish species, which also show no effect of dietary protein level on body protein levels (Jana et al 2006;Salhi et al 2004). Apparently, as long as the fish are getting enough energy for maintenance from nonprotein sources, and enough protein for production, their body protein content will not change.…”
Section: Discussionsupporting
confidence: 82%
“…Trypsin activity decreased with increasing dietary protein levels. A reduction in trypsin activity has also been shown for other species when fish are fed diets with protein content in excess of their requirement (Jana et al 2006; Mohanta et al 2008).…”
Section: Discussionmentioning
confidence: 87%
“…Thereafter a trend for growth depression as the protein content of the diet was increased was observed, especially at 500 g kg −1 CP. Studies with several teleosts have reported similar growth responses in fish, with manifestation of growth depression in response to excessive levels of dietary protein (Papaparaskeva‐Papoutsoglou & Alexis 1986; Horn, Mailhiot, Fris & McClanahan 1995; Elangovan & Shim 1997; Yang et al 2002; Jana, Garg, Barman, Arasu & Patra 2006; Martínez‐Palacios et al 2007).…”
Section: Discussionmentioning
confidence: 98%
“…The growth efficiency of several fish species has been studied through variation of dietary protein levels, and the results have shown not only the relationships between dietary protein concentration and physiological parameters of consumption, growth, and protein content in body or muscle, but also shown certain increased levels of dietary protein limited consumption and growth of the fish recently, that is, [1][2][3][4][5][6][7][8][9]. Increased growth is usually not associated with an increase in protein deposition rate, that is, [10][11][12], but rather an increase in lipid deposition rate, that is, [8,13].…”
Section: Introductionmentioning
confidence: 99%